2019
DOI: 10.1002/berj.3587
|View full text |Cite
|
Sign up to set email alerts
|

The association between private tutoring and access to grammar schools: Voices of Year 6 pupils and teachers in south‐east England

Abstract: England has experienced recent growth in the prevalence of private tutoring (PT). The qualitative study reported in this article aims to explore the perceptions of 14 Year 6 pupils and their teachers from three state-maintained primary schools in East Kent on PT participation and its impact on grammar school admissions. Data were collected through individual and focus group interviews and pupils' drawings. The data revealed that teachers were not totally aware of the scale of PT in their classes and ascribed P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 33 publications
(45 reference statements)
0
24
0
1
Order By: Relevance
“…In England, Ireson and Rushforth (2011) mapped the nature and prevalence of the phenomenon in three transition points (year 6, 11 and 13) and found that 71% of students who ever had a private tutor claimed it was to do well in an entry exam into secondary school. Hajar (2020) documented how the existence of grammar schools in the UK contributed to the prevalence of private tutoring among year 6 students. Guill and Lintorf (2019) examined the role of high-stake testing at the transition to various lowersecondary tracks by comparing German federal states (Bundesländer), which differ in the level of selectiveness for the lower-secondary admissions.…”
Section: Shadow Education and Between-school Trackingmentioning
confidence: 99%
See 1 more Smart Citation
“…In England, Ireson and Rushforth (2011) mapped the nature and prevalence of the phenomenon in three transition points (year 6, 11 and 13) and found that 71% of students who ever had a private tutor claimed it was to do well in an entry exam into secondary school. Hajar (2020) documented how the existence of grammar schools in the UK contributed to the prevalence of private tutoring among year 6 students. Guill and Lintorf (2019) examined the role of high-stake testing at the transition to various lowersecondary tracks by comparing German federal states (Bundesländer), which differ in the level of selectiveness for the lower-secondary admissions.…”
Section: Shadow Education and Between-school Trackingmentioning
confidence: 99%
“…Loyalka and Zakharov 2016;Prakhov and Yudkevich 2019;Smyth 2009), but fewer studies (e.g. Ireson and Rushforth 2011;Hajar 2020) have examined this role of shadow education at lower levels of the education system.…”
Section: Introductionmentioning
confidence: 99%
“…The conceptualisation of shadow education as a third place builds upon, but does not echo, student-centred work on shadow education; for instance in the United Kingdom (Hajar, 2018(Hajar, , 2019, Bangladesh (Mahmud, 2019), andIsrael (Addi-Raccah, 2019). Whereas in such previous studies students report relatively negative student experiences regarding shadow education and its examination-orientedness, none of the participants in our study expressed such negative experiences.…”
Section: Discussionmentioning
confidence: 99%
“…By asking students to reflect on the goals they pursue and the benefits they perceive from attending shadow education, we try to unravel what it is that students seek and find in shadow education in comparison to the home and school context. Our examination of students' goals and benefits not only builds upon and extends earlier student-centred work on shadow education in Asian and North-American contexts (Chan & Bray, 2014;Forsey, 2013;Hajar, 2018Hajar, , 2019Kim & Jung, 2019;Mahmud, 2019), but can also enhance our understanding of the relatively unknown position shadow education occupies in students' academic lives.…”
mentioning
confidence: 87%
“…Consequently, families competing for access to prestigious higher education institutions for their children, who need to get high scores on high-stakes exams, tend to coach their children themselves, while some hire private tutors. These ambitious families, as Hajar (2019) suggests, hold the view that doing well academically is the clearest path to a better life and so sometimes employ private tutors as a tool to provide additional training in the key subjects required by universities for admission. However, students from disadvantaged households tend to find themselves in a less favourable position because they can afford little or no private tutoring (henceforth, PT) sessions, even with less qualified tutors, adding to their social disadvantage (Prakhov & Sergienko, 2020).…”
Section: Introductionmentioning
confidence: 99%